Diversity for Restoration (D4R) decision support tool - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The D4R tool was first piloted for the Colombian tropical dry forest, but recently extended to similar ecosystems in Peru, southern Ecuador, recently Burkina Faso, and soon Cameroon.